The Effect of Problem-Based Learning (PBL) through a Deep Learning Approach on Cognitive Learning Outcomes in Science and Social Studies (IPAS) at Elementary School - Putri Ferinda; Mustamiroh Mustamiroh; Taufik Hidayat; Iksam Iksam (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
The low optimization of science and social studies (IPAS) learning outcomes in elementary schools indicates the need for more meaningful and contextual learning models. This study aimed to analyze the effect of the Problem-Based Learning (PBL) model, using a Deep Learning approach, on fourth-grade students' cognitive learning outcomes. A quantitative, quasi-experimental design was employed. The research subjects comprised 54 students, divided into experimental and control groups. Data were collected using validated and reliable pretest and posttest instruments and analyzed using descriptive statistics, normality and homogeneity tests, N-Gain calculations, and an Independent Samples t-test. The results showed that the experimental class mean score increased from 42.41 to 66.39, while the control class improved from 45.00 to 63.15. The N-Gain score of 0.29 was categorized as low to moderate. Hypothesis testing yielded a p-value of 0.498 (>0.05), indicating no significant difference between the groups. However, the Deep Learning-based PBL model demonstrated a tendency to improve cognitive learning outcomes and has potential for sustainable classroom implementation.